Screening for Crude Oil Degrading Bacteria in Liquid Organic Waste (Effluent Samples): Oil Degrading Bacteria in Effluent Samples - Akpe, Azuka Ramanus; Ekundayo, Afe Omolola; Esumeh, Frederick Ikechukwu (Biological Sciences - PJSIR, 2014)